Efeitos do meio na estrutura conformacional e eletrônica de moléculas com grupos aceitador-doador - Franco, Leandro Rezende Franco (2016)
The combined use of the Sequential QM/MM method with the ASEC mean field approximation [1] and the Free Energy Gradient method [2] has been very successful in describing the electronic structure of molecules in solution [3]. The advantage of this combination is that it permits the usage of an atomic- level modeling of the whole system, in contrast to continuum models, and, at the same time, it is less computationally expensive than ab initio or QM/MM simulations, even allowing the employment of more sophisticated electronic structure methods. In this context, the present work deals with the study of conformational and electronic structure, in solvent medium, of two organic compounds, DMACA and Phenol Blue, which have in common the characteristic of having acceptor-donor groups. The study is conducted in the presence of nonpolar, polar protic and polar aprotic solvents. It is adopted as basic methodology the ASEC-FEG, but also it is made a study with a continuum method, namely PCM. The results show that the solvent effect causes a significant geometric distortion of the molecules of interest while causing an internal charge displacement from donor group to acceptor group. Both effects are more pronounced in protic and aprotic solvents but mainly in protic solvents, in which hydrogen bonds lead to a greater solute polarization. The absorption spectra of these molecules, calculated by TD-DFT (CAM-B3LYP), directly reflect these changes. For all solvents, the absolute values of electronic transitions and their respective solvatochromic shifts are in good agreement with the experimental results.